Impact of Breathing and Anatomical Constraints on Subxiphoid Epicardial Puncture: Insights From a Japanese Cohort - Natnicha Pongbangli; Hirotsugu Ikewaki; Kyoko Hoshida; Kyoko Soejima (Journal of Arrhythmia)
ABSTRACT Background The subxiphoid approach is increasingly utilized for epicardial interventions. Understanding the effect of respiration on the distance from the xiphoid process to the pericardium is essential for improving procedural safety and efficacy. Methods A cross‐sectional study was conducted on 51 patients undergoing preprocedural ultrasound imaging. Measurements were taken in the supine position during spontaneous breathing at end‐inspiration and end‐expiration, with the probe directed toward both the midline and the left shoulder. Differences between respiratory phases and probe orientations were analyzed. Results The mean xiphoid‐to‐pericardium distance increased significantly from inspiration to expiration for both probe orientations (midline: 42.2 ± 12.2 mm vs. 54.6 ± 14.1 mm, p < 0.001; left shoulder: 40.5 ± 12.3 mm vs. 51.2 ± 14.2 mm, p < 0.001). The expiration‐inspiration difference was greater with the midline direction (mean difference: 12.4 mm) than toward the left shoulder (10.7 mm). Probe direction affected measurements during expiration (p = 0.012) but not during inspiration (p = 0.104). The distance to the pericardium showed a positive correlation with body weight (r = 0.561), body mass index (r = 0.675), and chest dimensions, including anteroposterior (AP) (r = 0.477) and lateral diameters (r = 0.451). In contrast, the chest wall size index (lateral/AP ratio) was negatively correlated (r = −0.365). No significant difference in this distance was found between patients with and without chronic obstructive pulmonary disease. Conclusions Respiratory phase and anthropometric parameters significantly influence the distance to the pericardium. These findings may guide safer planning of subxiphoid epicardial procedures.